The relationship between transformational leadership and organisational performance as perceived by the academic administrators of higher education institutions in Kurdistan - Hussain, Nojdar M. Bahaaddin (Kulliyyah of Education, International Islamic University Malaysia, 2016)
The aim of this study is to examine the relationship between transformational leadership practices and organizational performance among the academic administrators in three public universities in Kurdistan region of Iraq. The respondents comprise of 216 academic administrators. The study is based on Bass model (2008) employing quantitative method to acquire the data which used Multifactor Leadership Questionnaire (MLQ). There are four components of Transformational Leadership namely Inspirational Motivation, Idealized Influence, Individual Consideration and Intellectual Stimulation. Organizational Performance in the study comprises Learning, Teaching, Internationalization, Social System and Behavior of Leadership. The findings revealed that all the four facets of Transformational leadership practices have satisfactory levels above the mean value of 3.00. The highest variable was the Intellectual Stimulation (m =3.52; SD =.531). Organizational performance have satisfactory values above the average mean of 3.00 and variable with highest value was Behavior of leadership (m =3.69; SD =.502). In addition, the results also show positive weak correlation between perceived Organizational Performance and Inspirational Motivation. A positive and weak correlation is also found between Intellectual stimulation and Organizational Performance. Similarly positive correlation is also found between Individual consideration and Organizational Performance. While there is a moderately weak correlation for the relationship between Idealized influence and Organizational Performance, a as well as the correlation between the components of Transformational Leadership and Organizational Performance, the regression analysis findings, show that the Idealized influence is positively and significantly related with organizational performance. The more the increase of Idealized influence the more the organizational performance will be successful at the institutions of higher learning. This study is significant because it gives a clear picture of the relation of transformational leadership and organizational performance. It is also significant because it highlighted the process taken by the government to improve the organizational performance particularly in the higher institutions of Kurdistan.